2022
DOI: 10.3390/polym14091879
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Selected Laser-Marking Parameters and Surface Conditions on White Polypropylene Moldings

Abstract: Laser marking of polymer materials is a technology that is increasingly used in industry. Polypropylene (PP) shows a low ability to absorb electromagnetic radiation in the near-infrared range (λ = 1064 nm). The paper presents the influence of the surface condition of white-colored polypropylene moldings on the efficiency of their marking with a laser beam. In addition, the operation of the commercial laser marking additive (LMA) Lifolas M 117009 UN, intended to support the process of laser marking of polyolefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The nature of the laser-material interaction and the quality of the laser marking are highly dependent on both the material composition and the laser settings. Some of the polymers receive additives to facilitate laser marking and improve the quality of the codes, such as PP [13], ABS [14,15], and PA [16]. Some authors have studied the performance of laser marking on the surface of polymeric materials added by nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the laser-material interaction and the quality of the laser marking are highly dependent on both the material composition and the laser settings. Some of the polymers receive additives to facilitate laser marking and improve the quality of the codes, such as PP [13], ABS [14,15], and PA [16]. Some authors have studied the performance of laser marking on the surface of polymeric materials added by nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Czyzewski et al [13] studied laser marking on PP-LMA surface. They observed that the low value of radiation power can influence the quality of marked codes.…”
Section: Introductionmentioning
confidence: 99%